Prevalence of Helicobacter pylori virulence genotypes among children in Eastern Turkey - Ozbey, Gokben; Dogan, Yasar; Demiroren, Kaan (Baishideng Publ Grp Co Ltd, 2013)
AIM: To identify the virulence genotypes of Helico-bacter pylori ( H. pylori) if present in children in Eastern Turkey and if those genotypes are mostly associated with severe clinical presentations. METHODS: A total of 49 H. pylori positive Turkish children (42 with antral nodularity and 7 with peptic ulcer) who underwent upper gastrointestinal endoscopy with abdominal symptoms during the period from March 2011 to September 2012 were enrolled in this study. Antral nodularity was diagnosed endoscopically by two of the authors. We determined for the presence of cagA, vacA, cagE, iceA and babA2 genotypes of H. pylori isolates in DNA obtained directly from frozen gastric biopsy samples by polymerase chain reaction test using specific primers. RESULTS: Of the 49 H. pylori isolates studied, 61.2%, 91.8%, 22.4%, 28.6%, 57.1% and 40.8% were positive for the cagA, vacA s1, cagE, iceA1, iceA2 and babA2 genes, respectively. We showed that the most common vacA subtype was s1a (79.6%). However, the s2 gene was found less frequently with an isolation rate of 8.2% of the H. pylori isolates. The genotypes iceA2 and vacA s1m2 were the most frequently found types in children with antral nodularity. In addition, the genotypes iceA1, babA2 and vacA s1m1 were found in similar ratios in all the H. pylori isolates obtained from children with peptic ulcer. The genotypes vacA s2m1 and s1c were not observed in any of isolates studied. CONCLUSION: This study showed that vacA s1m2, cagA and iceA2 were the most common genotypes, and no association between antral nodularity and genotypes was observed. (C) 2013 Baishideng. All rights reserved.
Keywords: Helicobacter pylori; Children; Genotype; Polymerase chain reaction